Impact Testing of Polymer‐filled Auxetics Using Split Hopkinson Pressure Bar1 . Issue 10 (8th May 2017) - Fíla, Tomáš; Zlámal, Petr; Jiroušek, Ondřej; Falta, Jan; Koudelka, Petr; Kytýř, Daniel; Doktor, Tomáš; Valach, Jaroslav
Abstract : In this paper, impact testing of auxetic structures filled with strain rate sensitive material is presented. Two dimensional missing rib, 2D re‐entrant honeycomb, and 3D re‐entrant honeycomb lattices are investigated. Structures are divided into three groups according to type of filling: no filling, low expansion polyurethane foam, and ordnance gelatine. Samples from each group are tested under quasi‐static loading and dynamic compression using Split Hopkinson Pressure Bar. Digital image correlation is used for assessment of in‐plane displacement and strain fields. Ratios between quasi‐static and dynamic results for plateau stresses and specific energy absorption in the plateau are calculated. It is found out that not only the manufactured structures, but also the wrought material exhibit strain rate dependent properties. Evaluation of influence of filling on mechanical properties shows that polyurethane increases specific absorbed energy by a factor of 1.05–1.4, whereas the effect of gelatine leads to increase of only 5–10%. Analysis of the Poisson's function reveals influence of filling on achievable (negative) values of Poisson's ratio, when compared to unfilled specimens. The results for the Poisson's function yielded apparently different values as the assessed minima of quasi‐static Poisson's ratio in small deformations are constrained by a factor of 15. Abstract : In this paper, additively manufactured auxetic lattices are subjected to impact loading using Split Hopkinson Pressure Bar (SHPB). Selected samples are filled with strain rate sensitive material. Digital image correlation is used for analysis of the deformation behavior of the samples. Influence of filling on the samples' stress–strain curves, negative Poisson's ratio, and strain‐rate sensitivity is investigated.